The role of abiotic factors on both mango infestation and Sternochetus mangiferae abundances in mango agroecosystems in Benin - Dassou, A.G.; Gnanvossou, D.; Hanna, R.; Bokonon-Ganta, A.H. (Springer, 2018)
To develop management strategies for the mango seed weevil (Sternochetus mangiferae), we surveyed infestation levels of the pest in three agroecological zones of Benin and determined the influences of abiotic factors on mango infestation levels and population dynamics in mango orchards at IITA-Benin from 2009 to 2011. We collected immature and mature fruits from the canopy and fallen fruits from under the canopy from three randomly selected trees per cultivar, per orchard. Samples were examined to determine the number of the mango seed weevil eggs to adults during the rainy seasons of three years of the study. Our results show that the highest abundance of both the weevil and its eggs was from March to May of each year. In the first year of sampling, the cultivar Eldon was more infested than the other two cultivars, while during the second and third years, the cultivar Alphonse was most infested. The occurrence of the weevil was almost nil in the hot agroecological zones, while for the mango cultivars of IITA-Benin the percentage of infested fruit increased or decreased according to the studied variables, such as temperature, rainfall, and relative humidity. We found that the period from March to May with low temperatures and high rainfall was favourable to the population increase of mango seed weevils. We discuss possible implications of our findings for the management of the pest.